2020
DOI: 10.1038/s41388-020-1261-0
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD82 drives acute myeloid leukemia chemoresistance by modulating protein kinase C alpha and β1 integrin activation

Abstract: A principal challenge in treating acute myeloid leukemia (AML) is chemotherapy refractory disease. As such, there remains a critical need to identify key regulators of chemotherapy resistance in AML. In this study, we demonstrate that the membrane scaffold, CD82, contributes to the chemoresistant phenotype of AML. Using an RNA-seq approach, we identified the increased expression of the tetraspanin family member, CD82, in response to the chemotherapeutic, daunorubicin. Analysis of the TARGET and BEAT AML databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 74 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…The RAS- mutant DLD-1 isogenic cell line was used to validate the biological relevance of CD82 in SL. CD82 , a tetraspanin family member, contributes to the chemoresistant phenotype of cancers [24] . To experimentally corroborate the CD82 dependency of KRAS -mutant cancer cells, we applied siRNA-mediated knockdown of CD82 and assessed the interaction of CD82 and KRAS based on MEK activation in CRC cell lines ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The RAS- mutant DLD-1 isogenic cell line was used to validate the biological relevance of CD82 in SL. CD82 , a tetraspanin family member, contributes to the chemoresistant phenotype of cancers [24] . To experimentally corroborate the CD82 dependency of KRAS -mutant cancer cells, we applied siRNA-mediated knockdown of CD82 and assessed the interaction of CD82 and KRAS based on MEK activation in CRC cell lines ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of CD82 is in turn strongly modulated by its three extracellular N -glycosylation sites [ 25 ]. Interestingly, the involvement of CD82 in the chemoresistance of AML has been recently proposed [ 26 ]. In this regard, glycomics studies on adriamycin-resistant AML cell lines have also reported the involvement of α-2,6 and α-2,8 sialylation on N -glycans in chemoresistance [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tetraspanin superfamily is known to be associated with the activation, ligand binding, and inside-out signalling of β1 integrins and can promote cancer cell survival (Kotha et al, 2008;van Spriel et al, 2012 As a result, DNA damage repair is activated and leads to chemoresistance and AML cell survival (Floren et al, 2020). In summary, integrin β1 subunit is implicated in the chemoresistance of leukaemia by chemotherapy efflux, intracellular signalling, and apoptosis inhibition.…”
Section: Integrinmentioning
confidence: 99%